Synthesis of Graphene Oxide from Sugarcane Bagasse by Using Modified Hummers Method as a Microwave Absorber - Rahma, Mila Devita; Ramli, -; Gusnedi, -; Yohandri, - (Department of Physics – Universitas Negeri Padang UNP, 2024)
Bagasse, a residue from sugarcane processing, is chosen as the raw material due to its potential as an environmentally friendly, inexpensive, and easily obtainable carbon source. The modified Hummers method is a modification of the original Hummers method, incorporating thermal treatment in the initial synthesis stage to enhance the efficiency and quality of synthesis. The thermal treatment aims to improve the efficiency and quality of the synthesized graphene oxide. The modification is carried out in the synthesis process to obtain a high-quality product with better efficiency. Furthermore, this modification can also reduce synthesis time and minimize the risk of damage to the raw material. After the synthesis process is completed, the produced graphene oxide is characterized using various analytical techniques, including Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The synthesized graphene oxide is then tested for its ability to absorb microwaves at X-band frequencies (8-12 GHz). The characterization results indicate that the synthesized graphene oxide possesses a homogeneous structure with thin graphene layers and a clean surface. Moreover, the graphene oxide also exhibits excellent microwave absorption properties at an X-band frequency of 10.16 GHz, with a reflection loss value of -23.94 dB, absorption coefficient of 93.65%, and absorption bandwidth of 1.13 GHz. The test results demonstrate that the graphene oxide derived from bagasse exhibits significant absorption capabilities towards microwaves at specific frequencies. This indicates the potential application of graphene oxide as an effective microwave absorber material.